Nitrogen Immobilization by Wood Fiber Substrates Strongly Affects the Photosynthetic Performance of Lettuce - Lingyi Wu; Ruohan Li; Juncheng Liu; Wenzhong Cui; Zhiyong Qi; Wanlai Zhou (Plants)
Wood fiber substrates are widely used as peat substitutes in horticulture, but the impact of their high carbon-to-nitrogen ratio on nitrogen immobilization and crop photosynthetic performance remains unclear. This study systematically examined the effects of wood fiber substrates on lettuce photosynthetic performance and underlying physiological mechanisms using pot experiments. Two substrate treatments—peat (control) and wood fiber—were combined with three nitrogen levels: low, medium, and high (63, 127, and 210 mg N·L−1). Results indicated that wood fiber substrates significantly reduced the availability of fast-acting nitrogen, leading to a substantial decrease in lettuce biomass (39.0–56.8%), total nitrogen content (7.2–39.9%), and chlorophyll content (13.7–36.2%). Chlorophyll fluorescence kinetics analysis revealed that wood fiber substrates impair photosystem function through multiple pathways. At the early stage (15 days), key effects included structural damage to the donor side of PSII(Photosystem II), indicated by L and K peaks, and inhibited electron transfer on the PSI(Photosystem I) acceptor side (δRo decreased by 15.08–27.90%, along with a reduction in WOI amplitude). The findings provide an important theoretical basis for optimising nitrogen management strategies for wood fibre substrates.